Thomas Fleshman house "Eglantine" at 205 Cascade Avenue, 1963. - (:unkn) unknown (Forsyth County Public Library)
WSJ 6-2-63 p.C1.
Thomas Fleshman house "Eglantine" at 205 Cascade Avenue, 1963. The house was built by Jesse Laughenour about 1900.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth